Estrategias didácticas para el desarrollo de la comprensión lectora de los estudiantes de Educación General Básica. - Cunuhay Pastueña, Alexandra Paulina (2021)
The development of this research work was established with the objective of devising didactic strategies to strengthen reading comprehension in sixth grade students of the "Narciso Cerda Maldonado" Educational Unit, taking into account that this allows to strengthen pedagogical actions within the situational context, creating opportunities From the reality in which each of the activities are developed within the educational environment, for this a bibliographic investigation was carried out in reliable sources addressing the subject matter to be investigated, with these topics the development of strategies was based that seek to motivate the student to read, develop appropriate reading habits, improve vocabulary acquisition, improve the style and personal process as readers, increase reading speed and promote the mastery of students to use resources that help to understand a text. To achieve all these goals, multiple strategies have been designed that include activities that Language and Literature teachers can apply in an open period, after which it is expected that students will have developed a taste for reading, and the ability to understand texts of any kind, if they are appropriate for your age. Thus, activities are proposed that do not consume too much time in the classroom, but that require the student to have time at home to practice reading; The criteria of specialists have been taken into account to validate the proposal, satisfactorily determining its pedagogical feasibility based on technical criteria, aimed at promoting a contribution to institutional pedagogical development.